Labor market effects of a youth summer employment program in Sweden - Daniel Knutsson; Björn Tyrefors (Research Institute of Industrial Economics (IFN), 2024)
We evaluate a non-targeted summer youth employment program (SYEP) for high school students aged 16-19 in Stockholm, Sweden, where public sector job offers were as good as randomly assigned. In contrast to previous studies evaluating SYEP that targeted groups with lower socioeconomic status, we find substantial labor market effects but no effects on education, crime, or health outcomes. However, income is negatively affected except during the program year. The penalty increases in absolute terms but does not change much in relative terms over time. The penalty is consistently statistically significant and large just after high school graduation but there are indications that the penalty attenuates at ages 24. The adverse effects are the largest for applicants not enrolled in an academic track, who are males, and with less educated mothers. Interestingly, the extensive margin (having a job) is not the critical factor. Instead, a SYEP job offer affects the probability of obtaining more qualified and fulltime employment after high school graduation. We argue that receiving a program job leads to less private-sector labor market experience, provides a negative signal, and disrupts (private) labor market connections, which is vital for those seeking a job just after high school.
Keywords: J13; J45; J38; J21; 330; Labor market programs; Youth unemployment; Summer employment; Random list; SYEP